Is the communication of corrective feedback related with athletes' perceived justice of the coach - de Backer, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Perceived justice of the coach is a key predictor of elite athletes` team identification and cohesion (De Backer, 2011). Considering the fact that both team identification and team cohesion have shown to be linked with performance (Carron, Colman, Wheeler, & Stevens 2002; Walumbwa, Cropanzano, & Hartnell, 2009), coaches must be concerned about their players` perception of fairness. Therefore, the aim of the present study was to examine if the communication style of corrective feedback (i.e., autonomy supportive or controlling) and the transparency of the coach would affect team athletes` perceived justice. Method: Elite female volleyball players (N = 56; M = 22.33) and elite male handball players (N = 35; M = 23.59) from Belgian top level teams completed one general and five weekly web-based questionnaires during consecutive midseason weeks. We used MLwiN software to perform the multilevel analyses. Results: The results showed that autonomy supporting corrective feedback positively predicted overall perceived justice (p<.01). In contrast, controlling corrective feedback negatively predicted perceived justice (p<.05). Furthermore, coaches` transparency was positively related to athletes` perceived justice (p<.01). This positive effect was stronger when coaches used controlling feedback than when they communicated their feedback in an autonomy-supportive way. Discussion: The style of providing corrective feedback and the transparency of the coach are significant predictors of team athletes` perceived justice of the coach. Our results might be explained by the fact that, players who get autonomy supporting feedback will understand the purpose of this feedback and as a result, perceive their coach as fair. However, players who get controlling feedback lack this understanding. Consequently, it is vital for coaches to be transparent and explain this controlling corrective feedback afterwards. Otherwise athletes can misinterpret the coach`s motives and intentions and perceive him as unfair.